Differential diagnosis of ameloblastic fibro-odontoma: case report and literature review. Issue 1 (January 2019) - Kurimoto, Takayuki; Yamanishi, Tadashi; Harada, Takeshi; Matsuoka, Keiko; Uematsu, Setsuko; Yamamoto, Yuri; Arimura, Yuki; Togawa, Takeshi; Inoue, Naoko; Nishio, Juntaro
Abstract: Ameloblastic fibro-odontoma (AFO) is an uncommon benign tumor of the jaws and mostly found in patients aged less than 20 years. In this report, we describe two cases of AFO in a 5-year-old girl and a 3-year-old boy. In both cases, radiographic images showed a well-defined unilocular radiolucency with partial radiopacity in their jaws. Lesions were removed under general anesthesia and histopathologically examined, which revealed then to be AFOs. Although unerupted teeth that came in contact with the lesions were left as is, no recurrence was observed postoperatively. A common aspect of both cases was that a presurgical pathological diagnosis, which is usually made on the basis of findings of presurgical biopsy under local anesthesia, was not possible because of their immaturity. Differential diagnoses of AFO include calcifying epithelial odontogenic tumor (CEOT), calcifying cystic odontogenic tumor (CCOT), adenomatoid odontogenic tumor (AOT), and complex odontoma (CO). As this includes tumors with a high risk of recurrence such as CEOT, an accurate clinical diagnosis is quite important. However, it was difficult to distinguish AFO from other tumors on the basis of clinical features including radiographic findings. Our review of literature revealed that there have been no reports of cases of CEOT and CCOT in patients aged less than 6 years, whereas AFO was frequently detected. We concluded that radiographic findings in combination with the patient's age were quite useful indicators for the differential diagnosis of AFO. Moreover, our case report supported the notion that impacted teeth adjacent to AFO can be preserved.